Biomechanical study of muscle movement in the process of football technical training - Yue, Y.; Yang, Y. (Journal of Mechanics in Medicine and Biology, 2020)
Study of biomechanical characteristics of muscles can provide an effective reference for the training of athletes. Football is a vigorous sport, and physical collision and damage are frequent during competition and training. In order to improve football skills and prevent sports injuries, 10 athletes from Sport College of Shaoyang University, Hunan, China, were tested for isokinetic muscle strength. The moment of flexors and extensors was measured when the flexion and extension angular speed of hip and knee joints was 50°, 100°, 150°, 200°, 250°, 300°, 350° and 400°, respectively. Moreover the characteristics of force moment of flexor and extensor were verified by testing the electromyographic signal of the flexor and extensor of the hip and knee joints with isokinetic concentric exercise using piezoelectric sensor. The results showed that the electromyographic signal of the flexor and extensor of the hip and knee joint decreased with the increase of angular velocity of isokinetic concentric exercise; the electromyographic signal obtained by the piezoelectric sensor verified the law that the output of the flexor and extensor decreased, the extensor of the hip joint had incoordination during rapid movement, and the output of the extensor was always larger than that of the flexor no matter how fast the extensor moved.